Can the Digital Transformation Solve the Complexity Challenge? Three Case Studies in the Valves Industry - Lino CODARA; Francesca SGOBBI (Communications of International Proceedings, 2021)
How can firms leverage on digital technologies to improve their survival odds in a challenging and competitive environment? And what explains the differences observed in adoption paths and usage patterns? This paper resorts to the concepts of resilience and complexity to justify the existence of differentiated yet effective approaches to the digital transformation by contrasting the success stories of three Italian companies in the valves industry. The hypothesis underlying this study is that digital technologies aligned with the resilience level of the adopting organisation support an appropriate engagement with the external environment. For all companies examined in this paper the digital transformation represents an evolutionary rather than a revolutionary process. In addition, the technological solutions adopted are consistent with internal resilience level and match external complexity.
Keywords: Digital transformation; Resilience; Complexity; Case studies